(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The modern approach in design seeks to preserve traditional concepts in creativity, but through the eyes of contemporary art. A complete design of a modular composition of a carved ceiling in the tradition and artistic techniques of Renaissance art is presented. It is combined with modern LED lighting to match the shape and composition of the wood carving. This project also preserves the cultural heritage of the dying craft of woodcarvers. The project was realized using a traditional carving technique. The lighting was installed and the calculated illuminance was tested, which corresponds to the design.